2014
DOI: 10.1159/000365093
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of a Novel Angiotensin-Converting Enzyme Inhibitor versus Captopril on Plasma Angiotensins after Myocardial Infarction

Abstract: The compound 4-tert-butyl-2,6-bis(thiomorpholin-4-ylmethyl)phenol (TBTIF) has molecular characteristics similar to angiotensin-converting enzyme (ACE) inhibitors of the sulfhydryl subclass. To assess its value as a new therapeutic agent, we performed a comparative analysis of the effect of TBTIF versus captopril on the circulating levels of angiotensin (Ang) peptides and bradykinin as well as ACE and ACE2 expression after myocardial infarction. Male Wistar rats were divided into four groups: (1) sham-operated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In a study involving 859 subjects with type 1 diabetes, circulating ACE2 levels were significantly higher in those who had a history of CHD [26], ACE2 seems to combat the adverse effects of activated RAS and, therefore, may be a compensatory mechanism in coronary atherosclerosis. Previous studies have shown that the expression of cardiac ACE2 was increased after myocardial infarction (MI) [39][40][41][42], the circulating ACE2 activities were also significantly increased in MI patients [43,44] and animal models [38]. Our results suggested that even though without acute myocardial injury there is an increase in circulating ACE2, which may reflect coronary underlying atherosclerosis rather than MI [45].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In a study involving 859 subjects with type 1 diabetes, circulating ACE2 levels were significantly higher in those who had a history of CHD [26], ACE2 seems to combat the adverse effects of activated RAS and, therefore, may be a compensatory mechanism in coronary atherosclerosis. Previous studies have shown that the expression of cardiac ACE2 was increased after myocardial infarction (MI) [39][40][41][42], the circulating ACE2 activities were also significantly increased in MI patients [43,44] and animal models [38]. Our results suggested that even though without acute myocardial injury there is an increase in circulating ACE2, which may reflect coronary underlying atherosclerosis rather than MI [45].…”
Section: Discussionsupporting
confidence: 52%
“…As is mentioned above, Ang-(1-7) and Ang-(1-9) have been proposed to be important mediators in cardioprotection [51]. A series of studies demonstrated that both plasma and myocardial tissue levels of Ang-(1-7) significantly increased in myocardial infarction [41,52]. In contrast, another study indicated that the circulating levels of Ang-(1-9), but not Ang-(1-7) levels, increased 1 week after myocardial infarction [38].…”
Section: Discussionmentioning
confidence: 95%
“…This difference between compounds may be due to the difference in the efficacy. 9,35 This effect induced by TBTIF may in turn increase the Ang-(1-7) and Ang-(1-9) from Ang I and Ang II. 36,37 This property of TBTIF may be a consequence of better therapeutic effects than captopril.…”
Section: Discussionmentioning
confidence: 99%
“…7 One of these agents is 4-tert-butyl-2,6-bis(thiomorpholin-4-ylmethyl)phenol (TBTIF), and it was obtained by changing the pyrrolidine rings to methylthiomorpholin rings and by taking the phenol and methylpyrrolidine rings as a structural requirement to show cardiovascular effects. [7][8][9][10] However, there is little evidence about its pharmacological properties. In this sense, docking studies showed that the compound, compared with captopril, has higher affinity for angiotensinconverting enzyme (ACE).…”
Section: Introductionmentioning
confidence: 99%
“…A rise in kinin levels stimulates the synthesis of prostaglandins [2]. It was also reported an increase in prostaglandin production after captopril administration [3]. Therefore, the prostaglandin system could be involved in the mechanism of action of ACE inhibitors.…”
Section: Introductionmentioning
confidence: 95%